MODAL SOSIAL PEMBUAT KELAMAI DI DESA TIBAWAN KECAMATAN ROKAN IV KOTO - Ranti Yulias Fitri; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Dodol kalamai is one of the traditional food in Tibawan Village, Rokan  IV Koto. Its made from glutinous rice, desiccated coconut, palm sugar, and authentic ingredients that most people love trying. It certainly needs the skill to make it, not just from the taste but also the marketing and cooperation, its social capital. The purpose of the research to know how social capital is constructed for making dodol with a kualitatif descriptive approach and use purposive sampling to design the informant. the other hand, the collection of data techniques used in research are observation, interview, and documentation. The conclusion is element of social capital to describe the making of dodol are network, norms, and trust, where the business always does for maintaining a relationship with another business to do not cheating. As well as the owner of raw food, delivery service, and the cooperation to make a little mistake. Good cooperation with customers. It makes the business of dodol kalamai always produce and maintain the existence. Keywords : Social Capital, Dodol Kelamai